Sources and turnover of organic carbon and methane in fjord and shelf sediments off Northern Norway - Sauer, Simone; Hong, Wei-Li; Knies, Jochen; Lepland, Aivo; Forwick, Matthias; Klug, Martin; Eichinger, Florian; Baranwal, Soma; Cremiere, Antoine; Chand, Shyam; Schubert, Carsten J. (Geochemistry, Geophysics, Geosystems, 2016)
Source at http://doi.org/10.1002/2016GC006296 A manuscript version of this article was part of Simone Sauer's doctoral thesis, which is available in Munin at http://hdl.handle.net/10037/9548 To better understand the present and past carbon cycling and transformation processes in methane-influenced fjord and shelf areas of northern Norway, we compared two sediment cores from the Hola trough and from Ullsfjorden. We investigated (1) the organic matter composition and sedimentological characteristics to study the sources of organic carbon (C org ) and the factors influencing C org burial, (2) pore water geochemistry to determine the contribution of organoclastic sulfate reduction and methanogenesis to total organic carbon turnover, and (3) the carbon isotopic signature of hydrocarbons to identify the carbon transformation processes and gas sources. High sedimentation and C org accumulation rates in Ullsfjorden support the notion that fjords are important C org sinks. The depth of the sulfate-methanetransition (SMT) in the fjord is controlled by the supply of predominantly marine organic matter to the sediment. Organoclastic sulfate reduction accounts for 60% of the total depth-integrated sulfate reduction in the fjord. In spite of the presence of ethane, propane, and butane, we suggest a purely microbial origin of light hydrocarbons in the sediments based on their low δ 13 C values. In the Hola trough, sedimentation and C org accumulation rates changed during the deglacial-to-post-glacial transition from approximately 80 cm ka -1 to erosion at present. Thus, C org burial in this part of the shelf is presently absent. Low organic matter content in the sediment and low rates of organoclastic sulfate reduction (only 3% of total depth-integrated sulfate reduction) entail that the shallow depth of the SMT is controlled mostly by ascending thermogenic methane from deeper sources.